Correction to: Diagnostic performance of four SARS-CoV-2 antibody assays in patients with COVID-19 or with bacterial and non-SARS-CoV-2 viral respiratory infections - Timo Huber; Philipp Steininger; Pascal Irrgang; Klaus Korn; Matthias Tenbusch; Katharina Diesch; Susanne Achenbach; Andreas E. Kremer; Marissa Werblow; Marcel Vetter; Christian Bogdan; Jürgen Held (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Diagnostic performance of four SARS-CoV-2 antibody assays in patients with COVID-19 or with bacterial and non-SARS-CoV-2 viral respiratory infections - Timo Huber; Philipp Steininger; Pascal Irrgang; Klaus Korn; Matthias Tenbusch; Katharina Diesch; Susanne Achenbach; Andreas E. Kremer; Marissa Werblow; Marcel Vetter; Christian Bogdan; Jürgen Held (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
SARS-CoV-2 antibody assays are used for epidemiological studies and for the assessment of vaccine responses in highly vulnerable patients. So far, data on cross-reactivity of SARS-CoV-2 antibody assays is limited. Here, we compared four enzyme-linked immunosorbent assays (ELISAs; Vircell SARS-CoV-2 IgM/IgA and IgG, Euroimmun SARS-CoV-2 IgA and IgG) for detection of anti-SARS-CoV-2 antibodies in 207 patients with COVID-19, 178 patients with serological evidence of different bacterial infections, 107 patients with confirmed viral respiratory disease, and 80 controls from the pre-COVID-19 era. In COVID-19 patients, the assays showed highest sensitivity in week 3 (Vircell-IgM/A and Euroimmun-IgA: 78.9% each) and after week 7 (Vircell-IgG: 97.9%; Euroimmun-IgG: 92.1%). The antibody indices were higher in patients with fatal disease. In general, IgM/IgA assays had only limited or no benefit over IgG assays. In patients with non-SARS-CoV-2 respiratory infections, IgG assays were more specific than IgM/IgA assays, and bacterial infections were associated with more false-positive results than viral infections. The specificities in bacterial and viral infections were 68.0 and 81.3% (Vircell-IgM/IgA), 84.8 and 96.3% (Euroimmun-IgA), 97.8 and 86.0% (Vircell-IgG), and 97.8 and 99.1% (Euroimmun-IgG), respectively. Sera from patients positive for antibodies against Mycoplasma pneumoniae , Chlamydia psittaci , and Legionella pneumophila yielded particularly high rates of unspecific false-positive results in the IgM/IgA assays, which was revealed by applying a highly specific flow-cytometric assay using HEK 293 T cells expressing the SARS-CoV-2 spike protein. Positive results obtained with anti-SARS-CoV-2 IgM/IgA ELISAs require careful interpretation, especially if there is evidence for prior bacterial respiratory infections.

Characterization of a simplified ice-free cryopreservation method for heart valves - Agnes J. T. Huber; Timo Aberle; Martina Schleicher; Hans-Peter Wendel; Kelvin G. M. Brockbank (Cell and Tissue Banking, 2013)